Chemistry at the interior atoms of polycyclic aromatic hydrocarbons. (21st September 2015) - Scott, Lawrence T.
<x xml:space="preserve">Abstract</x> Reactions that form new σ-bonds to interior carbon atoms of polycyclic aromatic hydrocarbons were unknown before the fullerene era.